(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This review aimed to investigate how the teacher trainings in Gamification and Game-Based Learning has been developed and evaluated, through the systematization of empirical research on the subject, produced between 2010 and 2020. Searches were made using the keywords: teacher, professional development, teacher training, teacher education, game-based learning, education, gamification, in the EBSCO, ERIC, PsycINFO, ScienceDirect, Web of Science and Teses e Dissertações da CAPES databases. The final database consisted of 10 studies. The results indicate that most studies are not based on learning theories, there is low clarity about what the learning objectives are used, in addition to using poorly controlled designs, to the detriment of experimental ones. The state-of-the-art points to the need for more research to be carried out on the subject using adequate theoretical foundations and more sophisticated research designs.